Enhancing solid domestic waste management in Vietnam - Nguyen Quang Vinh (Journal of State Management, 2024)
Solid domestic waste management poses a critical challenge for authorities at all levels encompassing central and local government agencies, organizations, businesses, and the general public. Despite the availability of various policies and regulations in the field, issues persist due to rapid socio-economic development, inconsistent legal frameworks, and insufficient public awareness. These factors contribute to increasing problems such as waste accumulation, inadequate decomposition, environmental pollution, and public discontent. Failure to address these challenges effectively could severely affect ecological health and undermine green, clean, and sustainable development objectives.